Five new species and two new records of Erythroneurini from China (Hemiptera, Cicadellidae, Typhlocybinae) - Lin, Shuanghu; Zou, Hongfen; Huang, Min; Zhang, Yalin (Zootaxa, 2023)
Five new species and two new records of Erythroneurini are reported from China. The five new species, Dentaneura biangulata, Motaga rokfaoides, Seriana paraequata, Shibinga graciliprocessa and S. grossiprocessa spp. nov. are described and illustrated. Two new records from China, Alnetoidia pavo Dworakowska, 1994 and Empoascanara angkhangica, Hongsaprug, 1983, are also illustrated.